Alberta, migrants from Saskatchewan travelling to Fairview - Bowman, Isaiah, 1878-1950 (1932)
Same as XXXV-1. Migrant, Mr. Cook, traveling from southern Saskatchewan to Fairview, southwest of Peace River. Had traveled 2000 miles in 7 weeks. Field trip of 1932 Grayscale Bowman nitrate negative, box 16